1995
DOI: 10.1007/bf00169066
|View full text |Cite
|
Sign up to set email alerts
|

Processing of tetanus and botulinum A neurotoxins in isolated chromaffin cells

Abstract: Tetanus and botulinum A neurotoxins were introduced into the cytosol of chromaffin cells by means of an electric field in which the plasma membrane is forced to form pores of approximately 1 micron at the sites facing the electrodes. As demonstrated by electron microscopy, both [125I] and gold-labelled tetanus toxin (TeTx) diffuse through these transient openings. Dichain-TeTx, with its light chain linked to the heavy chain by means of a disulfide bond, causes the block of exocytosis to develop more slowly tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Attempts by others to examine the t1 ⁄2 of the LC of the closely related Clostridial neurotoxin, TeTx, in cultured spinal neurons, found that a highly radio labeled toxin disappeared long before even an initial onset of recovery from blockade of neurotransmission (44); the authors correctly suggest that degradation of TeTx LC (t1 ⁄2 ϭ ϳ6 days) may underlie the slow recovery from neuroinhibition. Indeed, it has been estimated that only 10 -100 intracellular toxin molecules are required to inhibit exocytosis (45), precluding straightforward radiolabeled detection; furthermore, this approach does not distinguish between relevant functional toxin protease in the cytosol and that which may reside in other cellular locations (i.e. endosomes).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts by others to examine the t1 ⁄2 of the LC of the closely related Clostridial neurotoxin, TeTx, in cultured spinal neurons, found that a highly radio labeled toxin disappeared long before even an initial onset of recovery from blockade of neurotransmission (44); the authors correctly suggest that degradation of TeTx LC (t1 ⁄2 ϭ ϳ6 days) may underlie the slow recovery from neuroinhibition. Indeed, it has been estimated that only 10 -100 intracellular toxin molecules are required to inhibit exocytosis (45), precluding straightforward radiolabeled detection; furthermore, this approach does not distinguish between relevant functional toxin protease in the cytosol and that which may reside in other cellular locations (i.e. endosomes).…”
Section: Discussionmentioning
confidence: 99%
“…Most significant is the inability to quantify cytosolic BoNT proteases within intoxicated cells using current detection methods. Although the number of cytosolic protease molecules necessary to inactivate exocytosis is not known, it has been estimated to be no more than about a thousand [34] for BoNT proteases, and less than ten molecules for the closely related tetanus toxin protease [35]. Even these remarkably low numbers may be overestimations as for other toxins such as ricin or diphtheria toxin, a single molecule has been shown sufficient to elicit a measurable effect (cell death) [36,37].…”
Section: Mechanisms Of Bont Persistencementioning
confidence: 99%
“…Indeed, it has been shown that, although the majority of disulfides are structurally inert in proteins, there are several disulfides that act as redox‐sensitive regulators 15, 16. The oxidation status of cross‐strand disulfides is believed to be important for the activity of toxins 17–19. Conserved cross‐strand disulfides occurring in viral fusion proteins and surface glycoproteins are believed to play a role in viral entry 20–24.…”
Section: Introductionmentioning
confidence: 99%